A high‐resolution monitoring station for the in situ assessment of nitrate‐related redox processes at an agricultural site. Issue 1 (21st November 2022) - Richard‐Cerda, Juan Carlos; Giber, Alexandra; Muñoz‐Vega, Edinsson; Kübeck, Christine; Berthold, Georg; Schüth, Christoph; Schulz, Stephan
Abstract: Biogeochemical redox processes control the chemical behavior of many major and trace elements, making their comprehension crucial for predicting and protecting environmental health. Nitrogen (N) is especially susceptible to changes in soil redox conditions and affects the cycles of other redox‐sensitive species. Elevated N concentrations, in nitrate form, in agricultural soils and associated freshwater ecosystems constitute a problem in many parts of the world. Although a wide variety of measures have been adopted, their assessment through concentration measurements in groundwater and surface water of the different monitoring networks has shortcomings. Nitrate, as a non‐point pollutant, is subject to several processes (e.g., transformation and retardation) before it is detected, making it impossible to evaluate measurements' effectiveness reliably. Thus, we designed and constructed a monitoring station featuring commercially available products and self‐manufactured components at an agricultural site for the in situ assessment of nitrate‐related processes by high‐resolution monitoring of hydraulic (soil water content, matric potential, groundwater head) and hydrogeochemical variables (oxidation‐reduction potential and groundwater and pore water chemistry) within the vadose zone and the shallow aquifer. The monitoring station has proven to be a reliable tool. Changes over depth and time of measured variables have been identified, allowing the detection of the transient behavior of the redox reactive zone and the interpretation of ongoing denitrification processes and other redox nitrate‐triggered phenomena, such as uranium roll‐front and selenium accumulation at the redox interface. Measuring both geochemical and soil water variables allows for the calculation of in situ solute inputs into the groundwater and their reaction rates. Core Ideas: We propose a robust design for long‐term, high‐resolution monitoring of soil hydraulic and hydrogeochemical variables. It features a combination of commercially available products and self‐manufactured components. Redox processes such as denitrification and uranium roll‐front propagation are observed.